Influence of Service Quality, Consumer Value, and Brand Image on Consumer Satisfaction at the Semarang Main Branch Post Office - Nurul - Amalia; Rustono - Rustono; Febrina - Indrasari (Politeknik Negeri Semarang, 2022)
The Post Office is one of the BUMN companies in services in the delivery of goods, letters, payments, and so on. The purpose of this research is to analyze the influence of service quality, customer perceived value, and brand image on customer satisfaction at post office Cabang Utama Semarang. The methods of data collection used in this research are questionnaires, observation, and literature review. The sample are 100 respondents calculated by Slovin formula. The sampling technique used purposive sampling of 100 respondents who are customer of Post Office Cabang Utama Semarang. The analytical method used int this researchis, multiple linear regression method. Based on calculations using SPSS version 26, the results shows that the regression equation was Y = 0,056X1+0,487X2+0,486X3+e. The result of this study explained that the variable service quality, customer perceived value, and brand image had positive and significant effect on customer satisfaction. The coefficient of determination in this research was 0,629 which means service quality, customer perceived value, and brand image affect the variable of customer satisfaction by 62,9%, while 37,1% is influenced by other variables not examined in this study